Results of open reduction and fixed angle locked volar plate fixation for fracture lower end of radius - Kumar, Gaurav; Vijay, Varun (International Journal of Research in Orthopaedics, 2019)
Background: The fracture of lower end radius is the most common fracture of upper extremity encountered in practice. Intra-articular fractures of distal radius present a challenging task to the operating surgeon. Open reduction and internal fixation using volar fixed-angle plates has shown to be a valid treatment option for unstable, dorsally displaced distal radial fractures. The present study was undertaken to evaluate the functional outcome of unstable distal radius fractures treated with fixed angle volar locking plate. Methods: The current study aimed at using fixed angle volar locking plate to treat unstable distal radius fractures. A total of 25 patients records were studied comprising of 19 males and 6 females with a mean of 44.5 years and followed up for a maximum of 1.5 year. Fractures were classified using the AO classification. The interpretation of functional outcome was done according to Mayo Wrist Score. Results: At final functional assessment, according to the Mayo wrist score, the scores of 6 patients were excellent, 10 patients good, 8 patients satisfactory and 1 patient poor. No non-union was reported in any patients. 3 patients developed minor complications in the form of superficial infection, hypertrophic scar and reflex sympathetic dystrophy and 1 patient developed major complication in the form of deep infection. Conclusions: Primary volar plate fixation of unstable distal radius fracture provides a stable construct that helps in early mobilization, better functional outcome and minimizes chances of complications and thereby is the treatment of choice for fracture distal end of radius.